Velamentous insertion cord in monochorionic twins isosexuales uniovulvares diamniotic - Chabez y Suárez, Álvaro (2015)
Insert a case velamentous Cord It comes in Pregnancy Gemelar UIniovulvar Monochorionic Diamnótico. No complications were recorded at delivery and the twins, both female, are born healthy. A review of the literature is made and the rarity of this anomaly umbilical cord insertion to uniovular asocaido diamnótico monochorionic twin pregnancy is stressed. A comment about the incidence, mechanism of production of this anomaly and the impact it brings in some cases the fetus is performed.